The Armchair quarterback syndrome: Do users pay attention to non-user-related feedback? - Babao, Charriz Dominique (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Digital Marketing and Analytics